Faktor-Faktor yang Mempengaruhi Dividend Payout Ratio pada Perusahaan Manufaktur di BEI - Sugianti, Sugianti; Tjondro, Subagyono (STIE Widya Manggala, 2013)
This study aimed to identify and analyze the factors that affected the dividend payout ratio on manufacturing companies listed in Indonesia Stock Exchange during the period of 2009-2012. The populations used in this study were 143 companies. Based on non probability technique with purposive judgment sampling method, the samples were determined 11 companies. The result of t-test showed that Company Size (X1), Likuiditas (Cash Ratio) (X2), and Debt to Equity Ratio (X3) had no significant effect on the Dividend Payout Ratio (Y). Meanwhile, Profitabilitas (Return on Assets) (X4) had significant effect on the Dividend Payout Ratio (Y). The result of F-test showed F Company Size (X1), Likuiditas (Cash Ratio) (X2), Debt to Equity Ratio (X3) and Profitabilitas (Return on Assets)s (X4) significantly affected the Dividend Payout Ratio (Y). Adjusted Square of 0.141 indicated 14.1%.